Marketing of native chicken in San Jose De Buenavista, Antique. - Gonzalez, Sheila J.; Tibudan, Ishmael (1997.)
This study describes and analyses the different marketing functions, costs, margins, problems, and channels encouraged by both producers and middlemen of native chicken in San Jose de Buenavista, Antique. Of the seven barangays sampled primary data are obtained from 33 producers and 13 middlemen. They are interviewed basing on their last transaction as of December 1996. , Results of the study show that out of the 512 heads of native chicken harvested by the producers, buyers operating outside San Jose de Buenavista Antique absorbed the biggest number of heads at 54 (277 heads), while the least number of heads was taken by the panting-retailer at 2 (10 heads). The highest price per head of native chicken is handled by the pantings at P18.00, while panting-retailer offered the lowest price per head of native chicken, which is P65.00. Despite the marketing costs and opportunity costs on labor incurred by the producers, still they get a positive financial net farm price at P71.55 per head of native chicken. Four types of middlemen are observed in this study, namely: producer-retailer, pantings, panting-retailer, and retailers--who performed interlocking functions. In terms of volume sold, the pantings absorbed the bulk of 63 (164 heads) and the least is absorbed by the panting-retailer at 6 (15 heads). But in terms of price received, the retailer took the highest average selling price at P96.67 head of native chicken and the lowest price which is P90.00/hd is handled by both the producer-retailer and the panting-retailer. All types of middlemen received positive gross margins, financial net margins, and financial net returns. Of the different marketing problems cited, majority of the producers cited low price of product as their major problem while middlemen considered no definite buyer as their major problem. The study recommends that respondents should have a cooperative, a standardized weighing system, and should ask financial and technical assistance from the government . To lessen marketing costs incurred by the middlemen, this study also suggests, that they should specialize only on a particular function (e.g. panting or retailer---alone).
Research Project (Undergraduate, Bachelor of Arts in Economics-Management) College of Arts and Sciences, University of the Philippines in the Visayas.
Keywords: Chicken, Native -- Marketing -- San Jose de Buenavista, Antique